Tuberculous and brucellosis meningitis differential diagnosis - Erdem, Hakan; Senbayrak, Seniha; Gencer, Serap; Hasbun, Rodrigo; Karahocagil, Mustafa Kasim; Sengoz, Gonul; Gorenek, Levent (Elsevier Sci Ltd, 2015)
Background: The Thwaites and Lancet scoring systems have been used in the rapid diagnosis of tuberculous meningitis (TBM). However, brucellar meningoencephalitis (BME) has similar characteristics with TBM. The ultimate aim of this study is to infer data to see if BME should be included in the differential diagnosis of TBM when these two systems suggest the presence of TBM. Method: BME and TBM patients from 35 tertiary hospitals were included in this study. Overall 294 adult patients with BME and 190 patients with TBM were enrolled. All patients involved in the study had microbiological confirmation for either TBM or BME. Finally, the Thwaites and Lancet scoring systems were assessed in both groups. Results: The Thwaites scoring system more frequently predicted BME cases (n = 292, 99.3%) compared to the TBM group (n = 182, 95.8%) (P = 0.017). According to the Lancet scoring system, the mean scores for BME and TBM were 9.43 +/- 1.71 and 11.45 +/- 3.01, respectively (P < 0.001). In addition, TBM cases were classified into probable category more significantly compared to BME cases, and BME cases were categorized into the possible category more frequently. Conclusions: When the Thwaites or Lancet scoring systems indicate TBM, brucellar etiology should also be taken into consideration particularly in endemic countries. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Brucellosis; Tuberculosis; Meningitis; Diagnosis